Salivary Gland Disorders in Pediatric Patients: A 20 Years’ Experience - Giorgio Lo Giudice; Paola Martina Marra; Chiara Colella; Angelo Itro; Gianpaolo Tartaro; Giuseppe Colella (Applied Sciences, 2022)
Salivary gland disorders are uncommon in children; they show a lower prevalence when compared to adults. The literature has a relative lack of information about the management and the different treatment protocols regarding these diseases. The aim of this research is to investigate the prevalence of both benign and malignant salivary gland disorders, focusing on diagnostic and therapy. An audit of patients diagnosed with salivary gland disorders was conducted from 2000 to 2020. 99 patients’ records were selected and analyzed: 51 males’ and 48 females’, age 10 ± 4 SD. Obstructive pathologies were the most frequently diagnosed (49 patients) followed by oncologic (21 patients), inflammatory (20 patients), rheumatologic (4 patients), malformative (3 patients) and infective disorders (2 patients). The parotid was the most affected major gland in 47 cases with a prevalence of diagnosis of juvenile recurrent parotitis (JRP) (40.4%), followed by the sublingual gland in 14 cases of ranula (100%) and the submandibular gland in 11 patients suffering from sialolithiasis (84.6%). Swelling was the most common symptom (75.7% of patients). Seven different neoplasms were documented. A greater prevalence of low-grade mucoepidermoid carcinoma among the malignant group (38.1% of oncologic cases) was noted. In regards to benign tumors, pleomorphic adenoma was the most common diagnosis (47.6% of cases). The symptoms and outcomes showed statistical significance concerning gender. Although salivary gland diseases in children and adolescents are rare, it is essential to observe and monitor all of the symptoms to intervene if necessary, as painless swelling is a symptom common from both benign and malignant diseases.